Tata Group and Air India : optimizing brands, routes, and operations in the airline portfolio - Sawhney, Mohanbir S.; Choudhury, Debdutta (London : Kellogg School of Management, 2023)
In January 2022, the Tata Group acquired Air India and Air India Express from the Indian government, marking the culmination of a long privatization process of the government-owned airlines. Before the Air India acquisition, the Tata Group already operated two airlines in the Indian market: Air Asia India and Vistara. Air India was a full-service domestic and international carrier with a large fleet; Vistara was a premium full-service domestic and international carrier with a limited fleet; and Air India Express and Air Asia India were low-cost carriers (LCCs).
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tata Group -- Management -- Case studies; Airlines -- Management -- Case studies; Transportation -- Mergers -- Case studies